(untitled) (European Journal of Education and Psychology, 2011)
The current research deals with the preparation and application of an assessment tool aimed at the early detection of drug use, bullying and mental disorders in Secondary Education students in school, family and spare time context. The assessment program we have designed uses 3D virtual environments to realistically recreate, in the style of current videogames, the contexts of drug abuse, bullying and family problems which usually occur during the teenage years. The Mii-School program consist of 17 stages of detailed three-dimensional simulation in which various avatars interact, causing problematic situations in which the participant must choose how he would behave, given the different response choices offered. The program then includes the different response styles of the participant in the situations presented. This would be very relevant from a preventive and therapeutic point of view, as it provides the possibility of knowing what persons would be in a risk situation and their responses in the above mentioned contexts.